Metodologia Agiliza - Marques, Márcia Soares (2021)
The world was suddenly taken over by a technological evolution that transformed the waypeople live, work and relate. Organizations like Uber, Amazon, Facebook, Google, Spotifyand Airbnb have put traditional management thinking in check, while so many othershave stood in the way of not keeping up with the new business dynamics. To keep upwith this evolution, traditional companies have been looking for agile methodologies totransform their form of management. According to PMI, inthe past 5 years, 71% of organizations report using agile approaches to their projectssometimes, often or always. In fact, between 2016 and 2017, one in five projects usedagile approaches, while another in five used hybrid or combined approaches. Championshave a keen focus on using agile approaches to projects - 55% versus 24% percentunderperforming. But just training the teams and implementing agile methodologies is notenough to achieve the success of the projects. Each organization has its own dysfunctions.It is also necessary to implement an immersion process in the teams in order to observethem closely and understand how they work, as Agile aims at some difficult goals suchas: satisfying customers through the "satisfaction of constantly changing requirements",which is not met by simple execution of agile practices. The objective of this master’s workis to develop a methodology that facilitates the work of agents of change in the processof transforming the traditional management model into agile, increasing the chances ofcompanies adapting to constant technological and business changes, focusing on in thedevelopment of an Agile culture.